(untitled) (Philology, 2024)
This paper discusses portraying of Amir Temur in Justin Marozzi’s book Tamerlane: Sword of Islam, Conqueror of the World. In this paper, our analyses aim to assist readers or researchers interested in understanding the character of Amir Temur, as portrayed by Justin Marozzi in his book. In this article, both qualitative and analytical methods were employed to analyze the portrayal of Amir Temur. This book is a detailed biography of the historical figure Tamerlane (Timur), who was a prominent Central Asian conqueror in the late 14th century. The book details Tamerlane’s military strategies and campaigns, highlighting his tactical genius and the vast territories he conquered, including parts of Persia, India, and Russia. Marozzi discusses Tamerlane’s influence on the regions he ruled, including his contributions to art and architecture, and how his legacy shaped subsequent empires. The book is written in an engaging narrative style, making it accessible to both general readers and those with a keen interest in history. Marozzi combines academic rigor with storytelling to bring Tamerlane’s life to life. Tamerlane’s selection as a main hero in literature stems from his multifaceted character, historical significance, and the rich thematic possibilities his life presents for exploration in various narrative forms. Tamerlane: Sword of Islam, Conqueror of the World offers a comprehensive and nuanced portrait of one of history’s most fascinating figures, making it a valuable resource for anyone interested in medieval history, military strategy, or the cultural history of Central Asia.